2016
DOI: 10.1097/md.0000000000005567
|View full text |Cite
|
Sign up to set email alerts
|

A case report with the peculiar concomitance of 2 different genetic syndromes

Abstract: Rationale:Down syndrome (DS) is the most common chromosome disorder in live born infants, affecting several body systems, but usually sparing skeletal muscles. We present the case of a child with coexistence of DS and dystrophinopathy. Only 1 similar case has been reported so far.Patient Concerns:An 8-year-old boy with DS had a history of incidental finding of increased serum creatine kinase levels up to 1775 U/L (normal values 38–174 U/L). He presented no delay in motor development; at the neurological examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…In addition, nonsense mutations in the dystrophin gene can, in some cases, be rescued by in-frame exon skipping, carrying a milder BMD phenotype [4]. A similar case with the concurrent identification of a very mild myopathic phenotype caused by DMD exon 15 skipping in a patient with Down syndrome has been recently reported [16]. Immunohistochemistry of dystrophin showed the correct dystrophin localization at the sarcolemma, with only weaker immunostaining with rod-domain specific antibodies.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, nonsense mutations in the dystrophin gene can, in some cases, be rescued by in-frame exon skipping, carrying a milder BMD phenotype [4]. A similar case with the concurrent identification of a very mild myopathic phenotype caused by DMD exon 15 skipping in a patient with Down syndrome has been recently reported [16]. Immunohistochemistry of dystrophin showed the correct dystrophin localization at the sarcolemma, with only weaker immunostaining with rod-domain specific antibodies.…”
Section: Discussionmentioning
confidence: 86%
“…Starosta [Starosta et al, 2022] described a case of a child diagnosed with Pompe disease and sickle cell anemia. Lerario [Lerario et al, 2016] reported a boy with Down syndrome and increased CK levels that yielded a co-diagnosis of Becker muscular dystrophy. Xia [Xia et al, 2021] reported variants in two genes in a patient presenting with both manifestations of spinal muscular atrophy and Duchenne muscular dystrophy.…”
Section: Discussionmentioning
confidence: 99%
“…В результате применения МПС стали выявляться как сочетания заболеваний, клинические проявления которых уже отмечены у больных, так и сочетания заболеваний, одно из которых манифестирует в более позднем возрасте и диагностируется до развития клинических проявлений [1,2]. Кроме того, описано сочетание у одного больного моногенного заболевания и хромосомного синдрома [3,4]. Для уточнения диагноза могут быть использованы различные молекулярные и цитогенетические методы: аллель-специфичная мультиплексноая лигаза-зависимая ПЦР (MLPA), МПС, исследование кариотипа с использованием дифференциальной окраски и хромосомный микроматричный анализ.…”
Section: Introductionunclassified